2018
DOI: 10.1590/0100-6991e-20181276
|View full text |Cite
|
Sign up to set email alerts
|

Glucose level evaluation in monopedicled rectus abdominis myocutaneous flap after venous occlusion: experimental study in rats

Abstract: It is possible to measure glucose levels in vertical myocutaneous rectus abdominis flaps of Wistar rats, perfused or congested, using a common glucometer. The diagnostic criteria that compare the glucose levels in the flaps with the systemic ones were more accurate in the evaluation of tissue perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(45 reference statements)
0
3
1
Order By: Relevance
“…To clarify the diagnostic criteria of flap congestion with high specificity and sensitivity, several new indexes have been created, including the rate of decline of systemic glucose and the differences between systemic and interstitial glucose levels. 14,19 However, the systemic glucose of diabetic rats in the present study was found to fluctuate during anesthesia, surgery, and monitoring. Therefore, unstable systemic glucose cannot be included as a diagnostic criterion.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…To clarify the diagnostic criteria of flap congestion with high specificity and sensitivity, several new indexes have been created, including the rate of decline of systemic glucose and the differences between systemic and interstitial glucose levels. 14,19 However, the systemic glucose of diabetic rats in the present study was found to fluctuate during anesthesia, surgery, and monitoring. Therefore, unstable systemic glucose cannot be included as a diagnostic criterion.…”
Section: Discussioncontrasting
confidence: 52%
“…The present results showed that the interstitial glucose of the flaps in nondiabetic rats consistently decreased to the lowest level at 56.5 minutes, which is comparable to previous studies. 14,21,23 However, in diabetic rats, the time taken for the interstitial glucose to decrease to its lowest level was doubled to 120.8 minutes. A possible explanation is that diabetes impairs cellular glucose metabolism and microcirculation in flaps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations